Spin-echo small-angle neutron scattering (SESANS) studies of diblock copolymer nanoparticles. Issue 1 (6th December 2018) - Smith, Gregory N.; Cunningham, Victoria J.; Canning, Sarah L.; Derry, Matthew J.; Cooper, J. F. K.; Washington, A. L.; Armes, Steven P.
Abstract : Concentrated dispersions of polymer nanoparticles with high contrast can be studied using SESANS in real space. Abstract : Poly(glycerol monomethacrylate)–poly(benzyl methacrylate) (PGMA–PBzMA) diblock copolymer nanoparticles were synthesized via polymerization-induced self-assembly (PISA) using reversible addition–fragmentation chain-transfer (RAFT) aqueous emulsion polymerization in D2 O. Such PISA syntheses produce sterically-stabilized nanoparticles in situ and can be performed at relatively high copolymer concentrations (up to 50 wt%). This PGMA–PBzMA formulation is known to form only spherical nanoparticles in water using aqueous emulsion polymerization ( Macromolecules, 2014, 47, 5613–5623), which makes it an ideal model system for exploring new characterization methods. The polymer micelles were characterized using small-angle X-ray scattering (SAXS) and a recently developed form of neutron scattering, spin-echo small-angle neutron scattering (SESANS). As far as we are aware, this is the first report of a study of polymer micelles by SESANS, and the data agree well with reciprocal-space scattering. Using this technique enables characterization of the concentrated, as synthesized dispersions directly without dilution, and this will provide a method to study self-assembled polymer systems that have concentration dependent morphologies, while still maintaining the advantages of scattering techniques.